Care trajectories and survival after discharge from specialized inpatient palliative care-results from an observational follow-up study - Kötzsch, Franziska; Stiel, Stephanie; Heckel, Maria; Ostgathe, Christoph; Klein, Carsten (Supportive Care in Cancer, 2014)
Background Little is known about the patients' individual care trajectories after discharge or transfer from inpatient palliative care units (PCU) to other care settings. This study aims to survey the further care trajectory and overall survival from the time of discharge of patients in a palliative care situation. Patient groups from either the PCU or the palliative care mobile support team (PCMT) are compared in order to analyze the demographic data, discharge settings, frequency of changes of care settings, overall survival from the time of discharge and place of death. Methods In a mono-centre prospective observational study, patients discharged or transferred from a German inpatient PCU or from other hospital wards with support of the PCMT were invited to participate in this study. After discharge, the central care provider, such as inpatient hospices, nursing homes or general practitioners, was asked for information on the care trajectory and on readmissions to hospital in four weekly follow-up phone calls until the patients' death. Place of death and overall survival from the time of discharge were noted. Results During the study period, 467 inpatients from the PCU and 554 inpatients from the PCMT were treated. Ultimately, 418 were discharged. Two hundred forty-five patients agreed to participate in the study, and the majority of them were either discharged home (60.8 %), to inpatient hospices (20.0 %) or to nursing homes (11.0 %). More than half of all of them (55.9 %) stayed continuously in their discharge setting. The remaining 44.1 % experienced a mean number of 3.1 ± 4.1 changes of care setting. Most frequently, patients changed their care setting from private home to hospital (N = 110; 32.4 %) and from hospital back to private home (N = 82; 24.4 %). Patients' mean overall survival from the time of discharge was 51.7 days (median 24.0 days, range 1-488 days). Most patients died in their private home (35.9 %), inpatient hospices (23.3 %) or inpatient PCUs (22.4 %). Conclusions The results show a high percentage of stable care trajectories at the end of life with few or no changes of care setting. To achieve this, well-considered discharge planning and an adequately chosen network of care providers are necessary. © 2014 Springer-Verlag Berlin Heidelberg.
Keywords: Care setting; Disease trajectory; Palliative care; Palliative care mobile support team; Treatment intensity